FRI0255 Injection of cd40 dna vaccine ameliorates the autoimmune pathology of non-obese diabetic mice with sjogren's syndrome. (12th June 2018) - Zhou, Y.-B.; Yuan, X.; Wang, Q.-K.; Zhang, H.; Wang, G.-S.; Li, X.-P.; Wang, Y.-P.; Li, X.-M.
Abstract : Background: In the patients with primary Sjögren's syndrome (pSS), overexpression of CD40 was reported. The increased CD40 expression contributes to enhance CD40-CD40L interaction and promotes the inflammatory response in various ways. Objectives: To investigate whether CD40 DNA vaccine could inhibit the immune response and slow the disease progression of SS in non-obese diabetic (NOD) mice. Methods: Female 8-week-old NOD mice were randomly divided into 3 groups. CD40 DNA vaccine group received pTaget CD40 DNA vaccine at a weekly dose of 50 ug for 4 weeks. Vector and NS group were administered an equivalent amount of empty vector or NS. Serum anti-CD40 antibody was measured by ELISA. Lymphocytes infiltration in the salivary glands was monitored by focus score (FS) calculation. Salivary CD40 was stained by immunohistochemistry. Splenic lymphocyte phenotypes were analysed by flow cytometry. CD40, TNF-α and IL-6 levels in the salivary glands were detected by PCR. Serum ANA was monitored by immunoflurescene. Results: 1) CD40 DNA vaccination induced anti-CD40 antibody response We found the positive rate on anti-CD40 antibody in vaccine group was 80% at week 6% and 100% at week 10, which was significantly increased compared with that in nonvaccinated ones.(p<0.05 and p<0.01, respectively) 2) Expression of CD40 decreased in salivary glands in vaccine group At week 10, CD40 expression on ductal epithelial and endothelial cells in NOD mice of vaccine group was significantly decreased positive staining. CD40 mRNA expression level showed a significantly reduction compared to vector group (0.51±0.31 vs. 1.56±0.53, p<0.05). 3) Down-regulation of lymphocytes infiltration in the salivary glands of mice in vaccine group At week 10, infiltration of lymphocytes was inhibited in treated group while increased in control group (F=5.275, P<0.05). FS was significantly decreased in vaccine group as compared to NS group (2.00±1.73 vs. 11.33±5.51, P<0.05). Average weight of wet salivary gland and the ratio of average salivary gland weight to body weight of NOD mice in vaccine group were significantly lower than that in control groups (p<0.05 and p<0.05, respectively). 4) CD40 DNA vaccine reduced the expression of TNF-α and IL-6 in the salivary glands In vaccine group, the expression level of TNF-α mRNA in salivary glands were declined significantly as compared to baseline (0.41±0.25 vs. 0.98±0.16, p<0.05) and IL-6 mRNA expression was down-regulated compared with control groups at week 10 (p<0.05; p<0.01, respectively). 5) Disturbances in spleen DC and plasma cell subpopulations At week 6, the total numbers of CD11c + DC decreased as compared with two control groups (p<0.05 and p<0.05, respectively). CD11c + DC and CD19 + CD138 + plasma cells were significantly reduced compared to basal level (p<0.01 and p<0.05, respectively). 6) Level of ANA reduced in the vaccine group At week 10, the expression of ANA in HEp-2 cells is strong positive (++++) in both control groups, but only positive (+) in vaccine group. Conclusions: These findings indicate that CD40 DNA vaccine can downregulate the expression of proinflammatory cytokines of TNF-α and IL-6, decrease the percentage of DCs and plasma cells, ameliorate the pathologic change in NOD mice with SS, and thus inhibit the autoimmune inflammation. Disclosure of Interest: None declared